STUDI PERENCANAAN PEMBANGKIT LISTRIK TENAGA MIKROHIDRO PADA SALURAN IRIGASI DESA ANGANTAKA ABIANSEMAL BADUNG - Ogik Parmana Putra, I Komang; Dwi Giriantari, Ida Ayu; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 10 No 1 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i01.p1, 2023)
The utilization of renewable energy can be a solution to meet the current increasing demand for electrical energy in rural areas, one of which is the use of water energy with the development of PLTMH. In this study, the planning of a microhydro power plant was carried out in the irrigation canal of Angantaka Abiansemal Badung Village as a source of electrical energy to meet the needs of electrical energy. The Angantaka Village irrigation channel has a head 2,1 meters, a width of 1,95 meters, an average depth of 0,88 meters and a water discharge of 0,3045 m3/s. The PLTMH planning system uses a breastshot wheel type water wheel with an efficiency of 75% and TEK STC-5 kW 3 phase AC synchronous generator and a 6 kW ELC control panel. Planning for PLTMH on the irrigation canal of Angantaka Abiansemal Badung Village with a capacity of 3,76 kW / 4,70 kVA. The initial investment cost required is IDR. 72.055.375 with operational and maintenance cost of IDR. 720.553 in one year.